Management of Pregnancy-Associated Thrombotic Thrombocytopenia Purpura - Fyfe-Brown, Ashley; Clarke, Gwen; Nerenberg, Kara; Chandra, Sujata; Jain, Venu (American Journal of Perinatology Reports, 2013)
Thrombotic thrombocytopenia purpura (TTP) is an infrequent but serious disease. Pregnancy is a known risk factor for presentation or relapse of TTP. Difficulties in differentiating TTP from preeclampsia/HELLP (hemolysis, elevated liver enzymes and low platelets) syndrome, and current treatment recommendations are discussed in this case report. A woman with previously treated and stable TTP had a relapse at 36 weeks' gestation. Careful surveillance led to an early diagnosis. Severe disease in the peripartum period was treated successfully with cryosupernatant plasma-based plasmapheresis and platelet transfusion, with good maternal and neonatal outcomes. Cryosupernatant plasma is a viable alternative to fresh frozen plasma for plasmapheresis for TTP and may offer some therapeutic and logistical advantages. Platelet transfusion can be undertaken safely if needed to prevent or treat significant hemorrhage.
Keywords: fresh frozen plasma; cryosupernatant plasma; platelet transfusion; preeclampsia; HELLP syndrome; TTP